Grab Your Future: Socialization in Constructing a Powerful English Application Letter for College Students - Herman, Herman; Sihombing, Sabar Dumayanti; Ervina, Nelly; Riny, Riny; Tannuary, Arwin; Berlien, Richard; Munthe, Bangun; Sirait, Tumpal Richardo; Bangun, Bangun; Butarbutar, Imelda (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2025)
In today’s competitive job market, the ability to compose a professional English application letter is essential for university graduates, especially in non-native English-speaking contexts. This study explores the implementation and outcomes of a socialization program designed to enhance the English correspondence skills of sixth-semester Management students at Sekolah Tinggi Ilmu Ekonomi (STIE) Sultan Agung, Pematangsiantar, Indonesia. A total of 75–80 students were divided into three groups (Group A, Group B, and Group C) and participated in a series of interactive workshops focused on the structure, language, and personalization of English application letters. Using a qualitative descriptive approach, data were collected through observations, document analysis of student letters, reflection essays, and post-program questionnaires. The results revealed significant improvements in students’ understanding of letter format, grammar usage, and the ability to tailor content to specific job advertisements. Peer review and collaborative learning played a crucial role in increasing student engagement and confidence in using English professionally. The discussion highlights the importance of genre-based instruction and social learning in developing employability-oriented communication skills. The findings emphasize the need for higher education institutions to embed practical, job-focused English training into their curriculum to better prepare students for real-world career demands. This study concludes that structured socialization programs can effectively equip students with the skills and confidence needed to construct impactful application letters, thereby enhancing their readiness for the job market. With the right support, students can take ownership of their career development, starting with how they present themselves on paper.